Using hierarchical DHTs to mitigate churn effects in mobile networks - Rocamora, Josyl Mariela B. (College of Engineering, University of the Philippines Diliman, 2014)
Existing flat peer-to-peer (P2P) systems based on distributed hash tables (DHTs) perform unsatisfactorily under churn due to their non-hierarchical topology. They experience low lookup success rate, high lookup latency and high bandwidth usage. We explore the use of hierarchical DHT (HDHT), specifically the superpeer design, in mitigating the effects of churn. To the best of our knowledge, we are the first to intensively examine HDHTs with and without churn. Using the OMNeT++ simulator and the OverSim framework, we analyze flat and hierarchical DHTs with and without churn. Results show that our HDHT implementations perform more satisfactorily than a flat DHT because of better fault isolation and smaller cluster sizes but at the cost of higher superpeer traffic. HDHTs are more stable as they have better lookup success ratios. They are more efficient as evidenced by lower lookup latencies and lower average node bandwidth usage. They are more scalable since their performance do not degrade even at high population. With this, our HDHT implementations can be utilized to alleviate the effects of churn in mobile networks.